2014
DOI: 10.1111/vcp.12134
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo‐hypoproteinemia in a hyperbilirubinemic dog with immune‐mediated hemolytic anemia

Abstract: A 10-year-old spayed female Miniature Poodle was presented to the University of Georgia veterinary teaching hospital for evaluation of lethargy, vomiting and anorexia of 4 days' duration. Physical examination, history and a minimum database led to a diagnosis of immune-mediated hemolytic anemia accompanied by marked hyperbilirubinemia. Refractometric protein determination was within the reference interval, whereas the biuret method indicated hypoproteinemia. This discrepancy was attributed to interference of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…There are 2 common analytic methods of determining plasma or serum total protein concentrations: biuret spectrophotometric assays and refractometry. A recent case report described a pseudohypoproteinemia in markedly icteric serum when the serum was assayed with a biuret total protein assay . However, the bilirubin concentration at which the interference becomes detectable was not established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are 2 common analytic methods of determining plasma or serum total protein concentrations: biuret spectrophotometric assays and refractometry. A recent case report described a pseudohypoproteinemia in markedly icteric serum when the serum was assayed with a biuret total protein assay . However, the bilirubin concentration at which the interference becomes detectable was not established.…”
Section: Introductionmentioning
confidence: 99%
“…A recent case report described a pseudohypoproteinemia in markedly icteric serum when the serum was assayed with a biuret total protein assay. 1 However, the bilirubin concentration at which the interference becomes detectable was not established. In the case report, the refractometric total protein concentration did not appear to be adversely affected by the hyperbilirubinemia.…”
Section: Introductionmentioning
confidence: 99%
“…These methods can have variable performance based on the number and type of protein species present in the sample, and minor interference can be caused by peptides and free amino acids . Additionally, icterus can cause interference with the biuret method . A survey revealed that only 2.4% of 842 participating human laboratories used refractometry‐based total protein quantification for SPE .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, pseudohypoproteinemia was reported in a hyperbilirubinemic dog. 21 The refractometer measurement was in the reference interval, whereas the biuret assay total protein concentration was decreased. The lower biuret assay total protein concentration was at-…”
mentioning
confidence: 99%